Curriculum planning management in higher education in Vietnam: The perspective of higher education institutions - Do, Thi Hoai Thu (Curtin University, 2013)
This study examined the extent to which the views, beliefs and attitudes of Vietnamese educators in the higher education sector are reflected in the practices associated with the current approach to curriculum planning management. The mixed-methods study, which focused on three universities in Vietnam, obtained data from documents, written questionnaires and semi-structured interviews. Findings from the study indicate a need to improve institutional autonomy and accountability in order to promote the effectiveness of curriculum planning management.